1997
DOI: 10.1089/cap.1997.7.17
|View full text |Cite
|
Sign up to set email alerts
|

Open Fluoxetine Treatment of Mixed Anxiety Disorders in Children and Adolescents

Abstract: An open-label pilot study examined fluoxetine treatment in 16 outpatients (9-18 years old) with mixed anxiety disorders. Following nonresponse to psychotherapy, fluoxetine monotherapy was started at 5 mg daily and was increased weekly by 5 or 10 mg daily for 6-9 weeks until improvement occurred or to a maximum of 40 mg (children under 12) or 80 mg (adolescents). Among patients on fluoxetine, severity of illness ratings were "much improved" (mean final Clinical Global Impression scale score 2.8 +/- 0.7). Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(49 citation statements)
references
References 24 publications
0
49
0
Order By: Relevance
“…They included 17 studies regarding AD trials in juvenile depressive disorders, with or without other psychiatric disorders (n = 2,637 subjects, 2,083 given an AD and 554 controls), 16 of which provided quantitative estimates of behavior outcomes considered as adverse events (see online supplementary table 1; for all online supplementary material, see www.karger.com?doi=10.1159/000345316) [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50]; 25 studies involved AD trials in juvenile anxiety disorders, with or without other psychiatric disorders (n = 4,130 subjects, 3,211 given an AD and 919 controls; online suppl. table 2) [51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76]. It is important to emphasize that interpretation of the findings is limited by the variety of types of patients and ages represented, and the range of behavioral outcomes considered to represent excessive arousal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They included 17 studies regarding AD trials in juvenile depressive disorders, with or without other psychiatric disorders (n = 2,637 subjects, 2,083 given an AD and 554 controls), 16 of which provided quantitative estimates of behavior outcomes considered as adverse events (see online supplementary table 1; for all online supplementary material, see www.karger.com?doi=10.1159/000345316) [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50]; 25 studies involved AD trials in juvenile anxiety disorders, with or without other psychiatric disorders (n = 4,130 subjects, 3,211 given an AD and 919 controls; online suppl. table 2) [51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76]. It is important to emphasize that interpretation of the findings is limited by the variety of types of patients and ages represented, and the range of behavioral outcomes considered to represent excessive arousal.…”
Section: Resultsmentioning
confidence: 99%
“…As in trials involving depression, outcomes ranged through insomnia, agitation or either subjective or objective physical restlessness, excitement or disinhibition, hypomania, or mania. Rates of such behavioral outcomes with AD treatment ranged from 0.7 to 2.4% for mania in 4 reports [56,65,66,68] to as high as 45-55% for insomnia, restlessness, agitation or irritability [52,57,59], and even 83% in 1 study reporting on unspecified behavioral reactions [73]. Reported latency to such reactions averaged 5.0 ± 3.0 weeks (online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…An open-label pilot study of SSRIs in adolescents with panic disorder and comorbid disorders showed significant improvement with fluoxetine, paroxetine, and sertraline alone or combined with short-term clonazepam or lorazepam when panic disorder was severe [64]. Fluoxetine treatment in youth, including some with panic disorder, yielded improvement in panic symptoms with a mean dose of 24 mg of fluoxetine in children and 40 mg in adolescents [65]. A retrospective chart review in children and adolescents with panic disorder and comorbid disorders treated with paroxetine (range, 10-40 mg/d) found significant improvement in panic symptoms and functioning, and paroxetine was well-tolerated [66].…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…Fluoxetine was shown to be efficacious based on parental reports for a group of 15 children with selective mutism, of which 11 had social phobia [Black and Uhde, 1994]. Several open studies have shown beneficial effects of SSRIs in pediatric anxiety disorders [Birmaher et al, 1994;Dummit et al, 1996;Fairbanks et al, 1997]. Two large randomized controlled trials of SSRIs in pediatric anxiety disorders are in progress and multiple industry-sponsored trials of SSRIs in pediatric depression are underway.…”
Section: Treatmentmentioning
confidence: 99%